Resolutions of Analog Rainfall Records Relative to Chart Scales - Chery, Donald L, Jr. (Arizona-Nevada Academy of Science, 1976)
From the Proceedings of the 1976 Meetings of the Arizona Section - American Water Resources Assn. and the Hydrology Section - Arizona Academy of Science - April 29-May 1, 1976, Tucson, Arizona === Five rainfall distributions, four l-in rainfall depths and one 3-in rainfall depth were plotted on charts with five different combinations of time and depth scales. The plotted events were read on an analog-to-digital converter by four different researchers. Each reading of a plotted record was compared with the known simulated rainfall-rate distribution. The correspondence of the rainfall rates read from the charts with the actual rainfall rate distribution is measured by an integral squared error and correlation coefficient. The results showed a general correspondence between error and the chart scale and a strong influence of maximum recorded rate and rate distribution on the error. For the chart scales evaluated, error did not become more directly associated with scale, except when recorded rates were less than about 10 in/hr. Error was directly related to the number of points read in any given trace by the relation E = 16.3N^(-0•426).